Digital Collaboration in Christian Education: Synergy of Family, Church, and School in the Age of Technology - Delima Anria Maena Banjarnahor; Andar Gunawan Pasaribu; Lasmaria Lumban Tobing; Elisamark Sitopu (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The development of digital technology has not only transformed educational systems and methods in general, but also challenged the paradigm of Christian education based on relationships and spiritual values. In the fast-paced and connected digital era, collaboration between families, churches, and Christian schools is key to maintaining the relevance and effectiveness of faith education. This study aims to identify the main challenges faced in implementing technology in these three domains, explore emerging synergistic opportunities, and formulate practical strategies that can support digital collaboration based on Christian values. The research method used was a descriptive qualitative approach using literature studies and direct interviews with stakeholders from various backgrounds—pastors, evangelical teachers, and Christian religious leaders. The results indicate that the targeted and valuable use of technology can strengthen communication, expand access to faith learning, and create a more inclusive and collaborative Christian education ecosystem. However, supervision, human resource training, and contextual content design remain urgently needed to prevent technology from becoming a barrier to spiritual growth. This study provides practical and conceptual contributions for educators, churches, and families in integrating technology wisely for the faith growth of today's generation.